FLAVONOIDS NUTRACEUTICALS IN PREVENTION AND TREATMENT OF CANCER: A REVIEW - Lotha, Robert; Sivasubramanian, Arvind (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The objective of the study was to discuss the preventive and treatment of cancer from flavonoids nutraceuticals from our daily dietary source. There has been increasing interest in the research of flavonoids from dietary sources, due to growing evidence of the versatile health benefits of flavonoids through epidemiological studies. Numerous biological activities have been reported. Some clinical trials or meta-analyses have suggested positive associations between flavonoid intake and human health, Several findings have proven that dietary flavonoids to have anticancer properties. Flavonoids due to their nontoxicity in nature and vast, broad aspect of its benefits in biological activities have been intensively studied for their health benefits also added to its abundant availability in our daily diets, for example, green leaves, fruits, red wine, andÂ teaÂ vegetables.